Hybrid Second-Order Sliding-Mode Tracking Control for Acrobot - Puga, Sergio A. (2007)
In this paper we propose a variable structure controller to solve the tracking control problem of Acrobot. The controller consists of a swing-up phase and a stabilization phase. The desired trajectory is centered at the upright position, while the Acrobot starts from the stable position. A stability analysis of the closed-loop dynamic system in question was performed within the framework of Lyapunov functions. Simulation results show the effectiveness of the proposed controller. Index Terms—Acrobot, twisting algorithm, switching control.